Elicitores na produção, composição e ação biológica de metabólitos DELippia origanoides kunth (verbenaceae) - Silva, Gabriela Carinhanha (2017)
Lippia origanoides, native medicinal aromatic shrub, has broad range of biologic activities. Elicitation, stimulation of plant defense, aims to rise the pruction of active compounds. Thus, it aimed to investigate the production, composition and activity of metabolites from this specie under elicitation. Cultivated plants were sprayed with cell material suspension of Aspergillus niger (AN) and Fusarium oxysporum (FO), solution of hydrogen peroxide (SH2O2), and distilled water. Hydrodistilled essential oils (EO) from leaves (LEO) and from inflorescences (IEO) were quantified, analyzed by GC/MS and tested against microorganisms by broth microdilution. The content of total phenolics calculated asgallic acid equivalent and flavonoids calculated asquercetin equivalent, and free radical scavenging activity (FRSA) using DPPH• of methanolic extracts (ME) of the leaves, inflorescences, stem and root were measured by spectrophotometer. It was calculated the in vitro solar protection factor (SPF) of ME and of photoprotective formulations (PPF) with the more active extract by spectrophotometer. SH2O2 increased the IEO production. FO increased the bicyclogermacrene concentration on IEO. All elicitors increase the effectiveness of both EO against Candida albicans and Staphylococcus aureus, and to reduce the activity against Escherichia coli of these one. FO and SH2O2 reduced the phenolic compounds on ME of stem and root. FO reduced the content of flavonoids on ME of the root. FO increased the FRSA of ME of stem. SH2O2 and AN reduced the FRSA of ME of root. SH2O2 increased the SPF of ME of stem and inflorescence. The ME of inflorescence treated with SH2O2 raised the SPF of PPF containing synthetic active compounds. It is concluded that FO and SH2O2 have potentiality as elicitors of L. origanoides active compounds production